Analisis Bibliometrik Tren Publikasi pada Kajian Risiko Sistem Manajemen Keamanan Informasi - Rahmad, Nuraini; Nasirly, Riri; Arsi, Fadli; Nasution, Fachri Ibrahim (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Security risks cover all aspects, including users usually feel lost or there is a leak of personal data, so there are often complaints by users who feel dissatisfied with a company. Risk management of information security is a methodology to identify and assess security risks by implementing, controlling and handling risks to protect an organization's interests. This research examines the bibliometric characteristics and trends of articles on “Risk of Information Security Management System”. Data from the Scopus database was collected, published between 1987 and 2023. Through searching the Scopus database, 1,351 articles were found. Bibliometric analysis was conducted using the vosviewer tool to visualize the research trends of this study. “Risk Management” and ‘Information Security Management Systems’ articles were found in 165 institutions and 87 countries. The bibliometric analysis revealed that Norges Teknisk-Naturvitenskapelige University had the most “Risk Management” and “Information Security Management Systems” research publications, with a total of 28 documents.